Software Product Quality Evaluation Guide for Electronic Health Record Systems - Lima, Luis F. de; Huve, Cristiane A. G.; Peres, Leticia M. (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2020: Anais do XXXIV Simpósio Brasileiro de Engenharia de Software, 2020)
Software product quality evaluation is an important process that benefits the system developer and the end user. Software products in domain specific, such as those in the health field, need specific treatments for their evaluation. This article presents a proposal for adaptations of a generic software product quality evaluation guide to evaluate a software domain specific. For the adaptations, the MEDE-PROS software product quality evaluation guide, the ISO/IEC 25010:2011, and the SBIS/CFM certification for electronic health record (EHR) systems were used. The purpose of these adaptations was to obtain an update of the MEDE-PROS guide, allowing to inspect quality attributes in a EHR system. To demonstrate the applicability of the guide after the adaptations, two case studies were performed in three health information systems. With the preliminary results of the case study, it was checked that the adaptations made in the guide were consistent, updating the guide with the ISO/IEC 25010:2011 standard and making it specialist in EHR systems, contributing with system evaluation more effectively in both guide versions.